Ignorance of the crowd: dysfunctional thinking in social networks - Seeme, Fatima; Green, David; Kopp, Carlo (Frontiers in Communication, 2025)
Cognitive dysfunction, and the resulting social behaviours, contribute to major social problems, ranging from polarisation to the spread of conspiracy theories. Most previous studies have explored these problems at a specific scale: individual, group, or societal. This study develops a synthesis that links models of cognitive failures at these three scales. First, cognitive limits and innate drives can lead to dysfunctional cognition in individuals. Second, cognitive biases and social effects further influence group behaviour. Third, social networks cause cascading effects that increase the intensity and scale of dysfunctional group behaviour. Advances in communications and information technology, especially the Internet and AI, have exacerbated established problems by accelerating the spread of false beliefs and false interpretations on an unprecedented scale, and have become an enabler for emergent effects hitherto only seen on a smaller scale. Finally, this study explores mechanisms used to manipulate people's beliefs by exploiting these biases and behaviours, notably gaslighting, propaganda, fake news, and promotion of conspiracy theories.